Beyond Words there is a World : Examining the intricacies of Awkward Silence in Social Interaction - Shamim Bano; Abhinav Joshi (International Journal of Scientific Research in Science and Technology, 2024)
In everyday life, we encounter moments of awkward silence that can be discomforting yet revealing. These instances, often occurring during conversations or social interactions, offer glimpses into the intricacies of human communication. Awkward silence reflects a pause in dialogue, a fleeting moment where words seem to fail us, yet it speaks volumes about our emotions, relationships, and social dynamics. We experience a range of emotions when confronted with awkward silence – from unease and embarrassment to curiosity and introspection. It prompts us to reflect on the underlying reasons for the silence and our own reactions to it. Do we feel compelled to fill the void with meaningless chatter, or do we embrace the silence as an opportunity for deeper connection or reflection? Through the lens of the viewer, Awkward silence becomes a window into the complexities of human interaction, inviting us to navigate its nuances with empathy, understanding, and perhaps a hint of humor.
Keywords: Human Interaction; Nervousness; Communication; Curiosity; Unresolved Issues; Social Anxiety; Power Dynamics; Silence